2018
DOI: 10.1177/1054773818780102
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Hereditary Angioedema: Family Caregivers’ Experiences

Abstract: The aim of this study was to understand the experiences of family caregivers in the process of diagnosing hereditary angioedema. An interpretive and qualitative research methodology based on Gadamer's philosophical hermeneutics was carried out. Data collection took place between May 2015 and August 2016 and included a focus group and in-depth interviews with 16 family caregivers. Two themes define the experiences of family caregivers: "Family life focuses on identifying the problem" and "Discovering and coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…2 Department of Translational Medical Sciences and Center for Basic and Clinical Immunology Research (CISI), University of Naples Federico II, Naples, Italy. 3 Department of Medicine, University of Padua, Padua, Italy. 4 ASST Fatebenefratelli Sacco, Department of Biomedical and Clinical Sciences, "Luigi Sacco" Hospital, University of Milan, Milan, Italy.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Department of Translational Medical Sciences and Center for Basic and Clinical Immunology Research (CISI), University of Naples Federico II, Naples, Italy. 3 Department of Medicine, University of Padua, Padua, Italy. 4 ASST Fatebenefratelli Sacco, Department of Biomedical and Clinical Sciences, "Luigi Sacco" Hospital, University of Milan, Milan, Italy.…”
Section: Fundingmentioning
confidence: 99%
“…Frequency, severity and site of attacks are extremely variable among patients and also during the patient’s life, and identification of triggering events is usually difficult. Patients may experience difficulties in carrying out daily living activities because of frequent attacks or due to anxiety for an unpreventable event [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family caregivers are unsung heroes in persons with cardiovascular conditions. This was found to be true in the study by Granero-Molina and colleagues (2020). This research team investigated the family caregiving experiences of persons with hereditary angioedema.…”
mentioning
confidence: 66%
“…This qualitative study identified the impact of this diagnosis. First, trying to obtain a diagnosis then having to cope with the diagnosis and support their loved one (Granero-Molina et al, 2020). There is a significant role for nursing in supporting the person with hereditary angioedema and their family caregivers through education, nursing interventions and advocacy for research in rare diseases.…”
mentioning
confidence: 99%